Distinct Migratory Properties of M1, M2, and Resident Macrophages Are Regulated by αDβ2 and αMβ2 Integrin-Mediated Adhesion - Cui, Kui; Ardell, Christopher L.; Podolnikova, Nataly P.; Yakubenko, Valentin P. (Frontiers in Immunology, 2018)
Chronic inflammation is essential mechanism during the development of cardiovascular and metabolic diseases. The outcome of diseases depends on the balance between the migration/accumulation of pro-inflammatory (M1) and anti-inflammatory (M2) macrophages in damaged tissue. The mechanism of macrophage migration and subsequent accumulation is still not fully understood. Currently, the amoeboid adhesion-independent motility is considered essential for leukocyte migration in the three-dimensional environment. We challenge this hypothesis by studying the contribution of leukocyte adhesive receptors, integrins αMβ2 and αDβ2, to three-dimensional migration of M1-polarized, M2-polarized and resident macrophages. Both integrins have a moderate expression on M2 macrophages, while αDβ2 is upregulated on M1 and αMβ2 demonstrates high expression on resident macrophages. The level of integrin expression determines its contribution to macrophage migration. Namely, intermediate expression supports macrophage migration, while a high integrin density inhibits it. Using in vitro three-dimensional migration and in vivo tracking of adoptively-transferred fluorescently-labeled macrophages during the resolution of inflammation, we found that strong adhesion of M1-activated macrophages translates to weak 3D migration, while moderate adhesion of M2-activated macrophages generates dynamic motility. Reduced migration of M1 macrophages depends on the high expression of αDβ2, since αD-deficiency decreased M1 macrophage adhesion and improved migration in fibrin matrix and peritoneal tissue. Similarly, the high expression of αMβ2 on resident macrophages prevents their amoeboid migration, which is markedly increased in αM-deficient macrophages. In contrast, αD- and αM-knockouts decrease the migration of M2 macrophages, demonstrating that moderate integrin expression supports cell motility. The results were confirmed in a diet-induced diabetes model. αD deficiency prevents the retention of inflammatory macrophages in adipose tissue and improves metabolic parameters, while αM deficiency does not affect macrophage accumulation. Summarizing, β2 integrin-mediated adhesion may inhibit amoeboid and mesenchymal macrophage migration or support mesenchymal migration in tissue, and, therefore, represents an important target to control inflammation.